Organelle‐Selective Labeling of Choline‐Containing Phospholipids (CPLs) and Real‐Time Imaging in Living Cells. Issue 4 (22nd April 2021) - Tsuchiya, Masaki; Tamura, Tomonori; Hamachi, Itaru
Abstract: Choline‐containing phospholipids (CPLs), including phosphatidylcholine (PC) and sphingomyelin (SM), are the major components of mammalian cell membranes and play critical roles during a variety of cellular processes. However, intracellular dynamics of CPLs is poorly understood due to a lack of methods to trace CPL trafficking at organelle resolution. Here, we describe protocols that make it possible to fluorescently label CPLs at the targeted organelles and to monitor their movement within living cells using confocal microscopy. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : ER‐Golgi‐selective labeling of azide‐tagged CPLs for confocal imaging Basic Protocol 2 : Mitochondria‐selective labeling of azide‐tagged CPLs for confocal imaging